ALIH WAHANA NOVEL SEPERTI HUJAN YANG JATUH KE BUMI KARYA BOY CANDRA KE DALAM FILM SEPERTI HUJAN YANG JATUH KE BUMI - Nia Dwi Maretha; Junal; Mariam Ulfa (Jurnal Sastra Aksara, 2021)
The transformation want is a transition of literary works that are transferred to other media. For example, the transition from the novel Seperti Hujan Yang Jatuh Ke Bumi by Boy Candra into the Seperti Hujan Yang Jatuh Ke Bumi movie, directed by Lasja Fauzia Susatyo. With the transfer of this vehicle, slight changes occur in the ecranization process, such as a reduction in the story but does not eliminate the core of the story, this reduction can be done in the plot, setting, even characters and characterizations.